The Review of Research on 3D Model Reconstruction Based on Point Cloud Data - Shi, Dingnan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Point cloud-based 3D modeling is a cutting-edge technology that leverages point cloud data from sensors like lidar and cameras to recreate detailed 3D models of objects and environments. This paper serves to outline the fundamental route, key principles, and prevalent methods within this field, with a specific emphasis on the preprocessing registration techniques for point cloud data and the advancements in 3D model reconstruction technologies.Furthermore, the article will delve into foundational 3D reconstruction methodologies, categorizing them into optimization-driven approaches and interpolation or fitting strategies. By categorizing these methods, it becomes possible to address the limitations and challenges associated with each algorithm and propose potential enhancement strategies to overcome these obstacles.By refining existing techniques, developing novel methodologies, and enhancing computational efficiency, the future holds promise for significant advancements in the realm of 3D modeling through point cloud data. In the conclusion, we provide a summary and outlook for the entire paper.